Tunneling Design with Point to Point Protocol over Ethernet (PPPoE) using Mikrotik RB-941 (Case Study of SMK Taruna Bhakti): Tunneling Design with Point to Point Protocol over Ethernet (PPPoE) using Mikrotik RB-941 (Case Study of SMK Taruna Bhakti) - Ilham Wahyudi Siadi; Iskandar Fitri; Rini Nuraini (Jurnal Mantik, 2020)
Ministry of Services or in the sphere of education requires a reliable network and a network that is always ready at all times so it is necessary to plan Anticipation on the Internet network with this one method that wants to be developed using Point-to-Point Protocol over Ethernet (PPPoE) on the Router device . Point-to-Point Protocol over Ethernet (PPPoE) is a very reliable method for use on both small and large scale networks. because it's very effective like Dial Up is faster and access is very secure.